Physical education and sports with disabled (Education. Physical training. Sport, 1999)
Several articles which deal with the problems of sports with disabled persons - in general and especially in Lithuania. Articles: Adomaitiene R. & Mikelkeviciute J. THE NATIONAL MODEL OF DISABILITY AND ADAPTED PHYSICAL EDUCATION OF THE DISABLED [Abstract] Huovinen P., Kannas S. & Rintala P. PHYSICAL ACTIVITY FOR EVERYBODY - INCLUDING PERSONS WITH DISABILITIES [Abstract] Lindisiene D. & Murauskiene N. [PROBLEMS OF KAUNAS CITY SCOOLCHILDREN ILL WITH SCOLIOSIS] Article in Lithuanian [Abstract] Simons J., Vandecruys H. & Vandenbussche I. AGREEMENT ON PSYCHOMOTORIC DEVELOPMENT OF PSYCHATRIC CHILDREN [Abstract] Skurvydas A., Maciukas A., Baceviciene R. & Liaugminas A. [CHANGES IN CONTRACTILE PROPERTIES OF WRESTLERS SKELETAL MUSCLES DURING MAXIMAL INTERMITTENT ISOMETRIC CONTRACTIONS] Article in Lithuanian [Abstract] Stonkus S. [SPORTS CAREER AND QUALITY OF LIVING OF ELITE BASKETBALL PLAYERS] Article in Lithuanian [Abstract] Valuziene N. [THE INFLUENCE OF MASSAGE WITH BEES PRODUCT PROPOLIS ON THE TREATMENT OF LOCOMOTOR SYSTEM TRAUMAS] Article in Lithuanian [Abstract] Vanlandewijck Y.C., Daly D., Spaepen A., Theisen D. & Pétré L. BIOMECHANICS IN HANDRIM WHEELCHAIR PROPULSION: WHEELCHAIR-USER INTERFACE ADJUSTMENT FOR BASKETBALL [Abstract] Vanlandewijck Y.C., Van de Vliet P., Daly D., Theisen D. & Pétré L. COUNSELING IN DISABILITY SPORT [Abstract] Vitkiene I., Stasiulis A., Bogusas V. & Kusleikaits M. [CHANGES IN SEVERAL BLOOD MINERALS AFTER MAXIMAL FAST INCREMENTAL EXERCISE IN YOUNG TABLE TENNIS PLAYERS]